Doctorateness and the DBA: what next?. Issue 2 (27th March 2018) - Poole, Brian
Abstract : Purpose: The purpose of this paper is to examine the extent to which Doctor of Business Administration (DBA) programmes currently offered by UK universities are appropriate to the needs of all stakeholders, including those of the experienced business and management professionals who enrol on them. Design/methodology/approach: The paper proceeds to its conclusions by scrutinising DBA programme descriptors on UK university websites, by critically reviewing the content of recent academic papers on doctorates in the fields of business and management, and by considering current provision in the light of ongoing debates about the nature of "doctorateness" taking place in the field of doctoral education as a whole. Findings: On the basis of a detailed review of relevant scholarly literature and of UK university website material, the paper concludes by suggesting, among other things, three possible futures for the DBA: one in which essentially the status quo prevails; a second in which all doctorates carry the award title PhD (though with two variants); and a third in which, in response to views expressed elsewhere in Europe, the current "professional doctorate" in business administration is no longer referred to as a "doctorate" but takes on a new title. Originality/value: This paper is an original contribution to the debate about the value and purpose of professional doctorates (and, in particular of the DBA) to the professional development of experienced managers and to their skills in research and workplace problem solving and decision making.